THE ISSUE OF THE LEGAL FORCE OF THE RECOMMENDATIONS OF THE UKRAINIAN PARLIAMENT COMMISSIONER FOR HUMAN RIGHTS - Bagmet, Andrii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: the purpose of this article is to analyze the issue of the legal force of the recommendations issued by the Ukrainian Parliament Commissioner for Human Rights, to determine their legal status, and to propose improvements to the administrative and legal regulation of such recommendations in line with international standards and best practices from other countries. Research methods: this study employs a comprehensive methodological approach, including a formal legal analysis of legislative and subordinate acts of Ukraine (in particular, the Constitution of Ukraine and the Law of Ukraine «On the Ukrainian Parliament Commissioner for Human Rights» dated December 23, 1997, No. 776/97-VR), as well as administrative and legal norms. A comparative legal analysis of international human rights standards was conducted, including the Universal Declaration of Human Rights (1948), the European Convention on Human Rights (1950), and the Paris Principles («Principles relating to the Status of National Institutions»), adopted by the Vienna World Conference on Human Rights and the United Nations General Assembly in 1993. To assess the effectiveness of human rights protection activities, the statistical method was used based on official data published by the Office of the Commissioner. Logical and systemic methods were also employed to formulate conclusions and recommendations. Results: the analysis revealed several systemic shortcomings in the legal framework governing the Commissioner’s activities. The main issue identified is the insufficiently binding nature of the Commissioner’s recommendations. Discussion: to overcome these issues, the article proposes legislative improvements aimed at ensuring the effectiveness of implementing the Commissioner’s recommendations through enhanced accountability and transparency. These changes have the potential to significantly strengthen parliamentary oversight and make the Commissioner’s activities more effective and result-oriented, which would have a positive impact on the overall state of human rights in Ukraine.